Where Culture Takes Hold: "Overimitation" and Its Flexible Deployment in Western, Aboriginal, and Bushmen Children. Issue 6 (14th July 2014) - Nielsen, Mark; Mushin, Ilana; Tomaselli, Keyan; Whiten, Andrew
<x xml:space="preserve">Abstract</x> Children often "overimitate, " comprehensively copying others' actions despite manifest perceptual cues to their causal ineffectuality. The inflexibility of this behavior renders its adaptive significance difficult to apprehend. This study explored the boundaries of overimitation in 3‐ to 6‐year‐old children of three distinct cultures: Westernized, urban Australians (N = 64 in Experiment 1; N = 19 in Experiment 2) and remote communities of South African Bushmen (N = 64) and Australian Aborigines (N = 19). Children overimitated at high frequency in all communities and generalized what they had learned about techniques and object affordances from one object to another. Overimitation thus provides a powerful means of acquiring and flexibly deploying cultural knowledge. The potency of such social learning was also documented compared to opportunities for exploration and practice.